Analysis of Tourist Motivation in Cave Tubing Activities in Pindul Cave - Nufail Naisaburi, Muhammad; Khairune Nisa, An Nuur; Bahri, Iswan; Nurmala Fadin, Delfyan Intan (Ann Publisher, 2024)
A popular location for special interest tourism, Pindul Cave is situated in Desa Bejiharjo, Kecamatan Karangmojo, Gunungkidul, and offers cave tubing adventures. By gliding down the tunnel on inner tubes and taking in the beautiful karst scenery, tourists can partake in a sport called